Positive electrode active material for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for manufacturing positive electrode active material for non-aqueous electrolyte secondary battery

JP7641543B2Active Publication Date: 2025-03-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021574492
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2020-12-03
Publication Date
2025-03-07
Estimated Expiration
2040-12-03

Smart Images

  • Figure 0007641543000006
    Figure 0007641543000006
  • Figure 0007641543000001
    Figure 0007641543000001
  • Figure 0007641543000002
    Figure 0007641543000002
Patent Text Reader

Abstract

This positive electrode active material for nonaqueous electrolyte secondary batteries contains a lithium transition metal composite oxide which contains 80% by mole or more of Ni relative to the total number of moles of the metal elements excluding Li, and at least one of Mn and Al, while additionally containing at least one metal element that is selected from among Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr, wherein: the total amount of Mn and Al is 5% by mole or more relative to the total number of moles of the metal elements excluding Li; and with respect to a filtrate of a suspension, which has been prepared by adding 250 mg of the positive electrode active material to 10 mL of a 17.5 mass% aqueous solution of hydrochloric acid, dissolving the positive electrode active material therein by 2-hour heating at 90°C, and subsequently diluting the solution to 50 mL, the elution amount of S in the filtrate as determined by inductively coupled plasma mass spectrometry is 0.002 mmol or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, a non-aqueous electrolyte secondary battery using the positive electrode active material, and a method for producing the positive electrode active material. [Background technology]

[0002] Lithium transition metal composite oxides are generally used as positive electrode active materials for non-aqueous electrolyte secondary batteries such as lithium ion batteries. In recent years, lithium transition metal composite oxides with a high Ni content have been widely used as high-capacity positive electrode active materials. For example, Patent Document 1 discloses a method for producing a positive electrode active material in which at least one compound selected from a sulfate compound, a nitric acid compound, a boric acid compound, and a phosphoric acid compound is fixed to the surface of particles of a lithium transition metal composite oxide containing Ni, together with tungsten oxide, and the composite particles are heat-treated under an oxygen atmosphere. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-040383 A Summary of the Invention

[0004] In non-aqueous electrolyte secondary batteries such as lithium ion batteries, it is an important issue to improve the charge / discharge cycle characteristics. In conventional techniques including the technique disclosed in Patent Document 1, there is still room for improvement in the cycle characteristics of the battery. In the manufacturing method disclosed in Patent Document 1, when the Ni content ratio in the positive electrode active material is high, cation mixing occurs and the initial capacity is likely to decrease.

[0005] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure is a positive electrode active material that includes a lithium transition metal composite oxide that contains 80 mol % or more of Ni, relative to the total number of moles of metal elements excluding Li, and at least one of Mn and Al, and that contains at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr, in which the total amount of Mn and Al is 5 mol % or more relative to the total number of moles of metal elements excluding Li, and the amount of S eluted in the filtrate, as determined by inductively coupled plasma mass spectrometry, is 0.002 mmol or more, relative to the total number of moles of metal elements excluding Li, and the filtrate is obtained by adding 250 mg of the positive electrode active material to 10 mL of a 17.5 mass % aqueous hydrochloric acid solution, dissolving the solution by heating at 90° C. for 2 hours, and diluting the suspension to 50 mL.

[0006] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above-described positive electrode active material for nonaqueous electrolyte secondary batteries, a negative electrode, and a nonaqueous electrolyte.

[0007] A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes the steps of oxidizing and roasting a hydroxide containing at least Ni obtained by a crystallization method to obtain a composite oxide, mixing the composite oxide with a lithium compound and calcining the mixed particles to obtain a lithium transition metal composite oxide, and washing the lithium transition metal composite oxide with water, mixing the composite oxide with at least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate, and strontium sulfate, and heat-treating the mixture at a temperature of 150 to 280° C. under vacuum conditions.

[0008] The positive electrode active material according to the present disclosure can provide a nonaqueous electrolyte secondary battery with excellent charge-discharge cycle characteristics. That is, the charge-discharge cycle characteristics can be improved in a nonaqueous electrolyte secondary battery including a positive electrode active material containing 80 mol % or more of Ni relative to the total number of moles of metal elements excluding Li. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] As described above, in non-aqueous electrolyte secondary batteries such as lithium ion batteries, improving the charge / discharge cycle characteristics is an important issue. As a result of intensive research conducted by the present inventors to improve cycle characteristics with a focus on the positive electrode active material, it was found that the cycle characteristics of the battery are specifically improved when a predetermined amount of S is contained in the filtrate of a suspension in which a positive electrode active material is dispersed in a predetermined hydrochloric acid aqueous solution. It was found that this effect is expressed when the total content of Mn and Al in the positive electrode active material is 5 mol% or more. Although the detailed mechanism of the improvement in cycle characteristics is not clear, it is considered that the eluted component S originates from SO4, and the compound containing SO4 functions as a protective layer on the particle surface of the lithium transition metal composite oxide, suppressing the decomposition reaction of the electrolyte on the particle surface, thereby improving the cycle characteristics. It is assumed that when a predetermined amount of S is present in the filtrate, this function as a protective layer is fully expressed.

[0011] Hereinafter, with reference to the drawings, an example of an embodiment of the positive electrode active material for nonaqueous electrolyte secondary battery according to the present disclosure, the nonaqueous electrolyte secondary battery using the positive electrode active material, and the manufacturing method of the positive electrode active material will be described in detail. Below, a cylindrical battery in which a wound electrode body 14 is housed in a cylindrical battery case will be exemplified, but the electrode body is not limited to the wound type, and may be a laminated type in which multiple positive electrodes and multiple negative electrodes are alternately laminated one by one with separators interposed therebetween. In addition, the nonaqueous electrolyte secondary battery according to the present disclosure may be a prismatic battery having a prismatic metal case, a coin battery having a coin-shaped metal case, or the like, or may be a laminated battery having an exterior body composed of a laminate sheet including a metal layer and a resin layer.

[0012] Fig. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in Fig. 1, the nonaqueous electrolyte secondary battery 10 includes an electrode assembly 14, an electrolyte, and a battery case 15 that accommodates the electrode assembly 14 and the nonaqueous electrolyte. The electrode assembly 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound with the separator 13 interposed therebetween. The battery case 15 includes a cylindrical outer can 16 with a bottom, and a sealing body 17 that closes the opening of the outer can 16.

[0013] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles, amides, and mixed solvents of two or more of these may be used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. The non-aqueous electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte. For example, a lithium salt such as LiPF6 is used as the electrolyte salt.

[0014] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18, 19 disposed above and below the electrode body 14. In the example shown in Fig. 1, a positive electrode lead 20 attached to the positive electrode 11 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and a negative electrode lead 21 attached to the negative electrode 12 passes outside the insulating plate 19 and extends toward the bottom side of the outer can 16. The positive electrode lead 20 is connected to the lower surface of a bottom plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the bottom plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.

[0015] The exterior can 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 is formed with a grooved portion 22 that supports the sealing body 17, for example, a portion of the side surface of the exterior can 16 protruding inward. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface.

[0016] The sealing body 17 has a structure in which a bottom plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.

[0017] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material contained in the positive electrode 11, will be described in detail below.

[0018] [Positive electrode] The positive electrode 11 includes a positive electrode current collector and a positive electrode composite layer formed on at least one surface of the current collector. For the positive electrode current collector, a foil of a metal, such as aluminum or an aluminum alloy, that is stable in the potential range of the positive electrode 11, or a film having the metal disposed on the surface layer, can be used. The positive electrode composite layer contains a positive electrode active material, a conductive material, and a binder, and is preferably formed on both sides of the positive electrode current collector. The positive electrode 11 can be manufactured by applying a positive electrode composite slurry containing a positive electrode active material, a conductive material, a binder, and the like onto the positive electrode current collector, drying the coating, and then compressing the coating to form a positive electrode composite layer on both sides of the positive electrode current collector.

[0019] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).

[0020] The positive electrode active material contains 80 mol% or more of Ni relative to the total moles of metal elements excluding Li, and at least one of Mn and Al, and contains at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr. Here, the total amount of Mn and Al is 5 mol% or more relative to the total moles of metal elements excluding Li. The positive electrode active material is mainly composed of the complex oxide, and the content of the complex oxide in the positive electrode active material is preferably 90 mass% or more, and may be substantially 100 mass%. Note that the positive electrode active material may contain a lithium transition metal complex oxide other than the complex oxide or other compounds within a range that does not impair the effects of the present disclosure. Hereinafter, unless otherwise specified, the lithium transition metal complex oxide means the above complex oxide having a Ni content of 80 mol% or more.

[0021] The lithium transition metal composite oxide may contain 85 mol % or more of Ni, or may contain 90 mol % or more of Ni, based on the total number of moles of metal elements excluding Li. The Ni content is, for example, 80 to 95 mol %. An example of a suitable lithium transition metal composite oxide is represented by the general formula Li a Ni (1-x-y) M1 x M2 y O2 (0.97≦a≦1.2, 0.05≦x≦0.2, 0≦y≦0.1, 0.05≦x+y≦0.2, M1 is at least one of Al and Mn, and M2 is at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr). The lithium transition metal composite oxide may contain elements other than Li, Ni, metal element M1, and metal element M2, such as Na, V, In, Y, and Cr, within a range that does not impair the effects of the present disclosure.

[0022] The lithium transition metal composite oxide is generally a secondary particle formed by agglomeration of primary particles. The volume-based median diameter of the lithium transition metal composite oxide (secondary particles) is not particularly limited, but is preferably 2 μm to 20 μm, more preferably 6 μm to 15 μm. The volume-based median diameter of the composite oxide is a particle diameter at which the volume integrated value is 50% in a particle diameter distribution measured using a laser diffraction scattering type particle size distribution measuring device, and is also called the 50% particle diameter (D50). The particle diameter of the primary particles constituting the secondary particles is, for example, 0.05 μm to 2 μm. The particle diameter of the primary particles is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM).

[0023] The positive electrode active material containing the lithium transition metal composite oxide is prepared by adding 250 mg of the positive electrode active material to 10 mL of a 17.5 mass % aqueous hydrochloric acid solution, dissolving the material by heating at 90°C for 2 hours, and diluting the suspension to 50 mL. The filtrate has an amount of S eluted in the filtrate that is determined by inductively coupled plasma mass spectrometry (ICP-MS) of 0.002 mmol% or more. If the amount of S eluted does not satisfy this condition, good cycle characteristics cannot be obtained, as shown in the examples described later. The filtrate contains sulfate ions (SO4 2- ) may be present, and Li ions may be absent.

[0024] A specific method for quantifying the amount of the eluted components of the positive electrode active material is as follows. (1) 250 mg of the positive electrode active material is added to 10 mL of a 17.5% by mass aqueous hydrochloric acid solution, and the mixture is heated and dissolved at 90° C. for 2 hours to prepare a suspension in which the active material is dispersed in the aqueous solution. The temperature during the preparation of the suspension may be about 90° C., for example, 90° C.±5° C. (2) The suspension is filtered (solid-liquid separation) to obtain a filtrate containing eluted components such as S. Then dilute to 50 mL with distilled water. (3) The amount of the above eluted components in the filtrate is determined using an ICP-MS device.

[0025] The S in the filtrate is an eluted component derived from a compound containing SO4 (hereinafter, sometimes referred to as "SO4-containing compound"), and the positive electrode active material is considered to contain the SO4-containing compound. The SO4-containing compound is present, for example, on the particle surface of the lithium transition metal composite oxide. The SO4-containing compound may be present inside the secondary particles, that is, on the surface of the primary particles that are not present on the surface of the secondary particles (the interface between the primary particles), but is preferably present more on the surface of the secondary particles than inside the secondary particles.

[0026] The SO4-containing compound is preferably present at a uniform density over the entire surface of the lithium transition metal composite oxide particles. The SO4-containing compound present on the surface of the lithium transition metal composite oxide particles is assumed to function as a protective layer and suppress the decomposition reaction of the electrolyte on the particle surface. When the filtrate contains S at a concentration of 0.002 mmol or more, the function of the SO4-containing compound as a protective layer is fully exerted, and the cycle characteristics of the battery are considered to be improved.

[0027] The amount of S dissolved in the filtrate is preferably 0.003 mmol or more. The upper limit of the amount of S dissolved is not particularly limited from the viewpoint of cycle characteristics, but is preferably 0.24 mmol in consideration of battery capacity, output, etc. The amount of S dissolved is, for example, 0.003 to 0.03 mmol.

[0028] The amount of eluted metal element M (at least one metal element selected from Co, W, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr) contained in the filtrate is preferably 0.0001 mmol or more. The upper limit of the amount of eluted metal element M is not particularly limited from the viewpoint of cycle characteristics, but is preferably 0.3 mmol in consideration of battery capacity, output, and the like.

[0029] The SO4-containing compound present on the particle surface of the lithium transition metal composite oxide is assumed to be at least one selected from lithium sulfate, cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate, and strontium sulfate. For example, at least lithium sulfate is present on the particle surface of the lithium transition metal composite oxide. In addition, hydroxides or oxides of Co, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, Sr, etc. may be present on the particle surface of the lithium transition metal composite oxide.

[0030] The amount of Li contained in the positive electrode active material is preferably 7.4% by mass or less, more preferably 7.3% by mass or less, and particularly preferably 7.1% by mass or less. The amount of Li may be 7.0% by mass or less, but in that case, the charge capacity may decrease or the reaction resistance may increase. If the amount of Li exceeds 7.4% by mass, the positive electrode mixture slurry used to form the positive electrode mixture layer may gel, making it difficult to form a good positive electrode mixture layer. The occurrence of cation mixing can be suppressed and the amount of Li elution can be reduced by adding a specific sulfate compound to the lithium transition metal composite oxide washed with water and then heat-treating the mixture at a low temperature and in a vacuum state to produce a positive electrode active material.

[0031] In addition to the SO4-containing compound, at least one of tungsten oxide (WO3) and lithium tungstate produced by the reaction of excess Li of the lithium transition metal composite oxide with WO3 may be fixed to the particle surface of the lithium transition metal composite oxide. Like the SO4-containing compound, WO3 and lithium tungstate are preferably fixed uniformly and at a uniform density to the entire particle surface of the lithium transition metal composite oxide. When WO3 and lithium tungstate are present on the particle surface, the cycle characteristics of the battery are further improved by the synergistic effect with the SO4-containing compound. The content of WO3 and lithium tungstate is preferably 0.05 to 0.5 mol% in terms of W element relative to the total mole number of metal elements excluding Li in the lithium transition metal composite oxide. In order to minimize the decrease in charging capacity, it is particularly preferable that the content is 0.05 to 0.2 mol%.

[0032] The adhesion of WO3 and lithium tungstate to the particle surface of the lithium transition metal composite oxide and the content thereof can be observed and quantified using a SEM and an ICP emission spectrometer. Note that, on the particle surface of the lithium transition metal composite oxide, SO4-containing compounds and inorganic particles other than WO3 and lithium tungstate, such as phosphorus compounds, boron compounds, and rare earth compounds, may be present.

[0033] The positive electrode active material containing the lithium transition metal composite oxide is prepared by adding 1 g of the positive electrode active material to a mixed solution of 100 mL of pure water, 1 mL of 35 mass% hydrochloric acid aqueous solution, 0.05 mL of 46 mass% hydrofluoric acid, and 0.05 mL of 64 mass% nitric acid, stirring for 5 minutes, and then filtering the mixed solution. The ratio ((partial elution amount / total elution amount)×100) of the partial elution amount of the metal element M contained in the filtrate determined by ICP-MS to the total elution amount of the metal element M determined similarly when 1 g of the positive electrode active material is completely dissolved is preferably 50% or more, more preferably 55% or more. The partial elution amount measured by this method indicates the amount of the metal element M present on the surface of the positive electrode active material and in its vicinity (similarly for S). When the elution amount ratio of the metal element M satisfies the condition, the positive electrode active material exhibits superior cycle characteristics compared to when it does not satisfy the condition.

[0034] The total amount of eluted positive electrode active material is determined by adding 200 mg of positive electrode active material to a mixed solution of 5 mL of 35 mass% hydrochloric acid, 2.5 mL of 46 mass% hydrofluoric acid, and 2.5 mL of 64 mass% nitric acid, heating the mixed solution at about 90°C for 2 hours, adding pure water to make up to 100 mL, and measuring it by ICP-MS.

[0035] The above-mentioned positive electrode active material can be produced by a production method including the following steps. (1) A step of oxidizing and roasting a hydroxide containing at least Ni obtained by a crystallization method to obtain a composite oxide. (2) A step of mixing the composite oxide with a lithium compound and calcining the mixed particles to obtain a lithium transition metal composite oxide. (3) A process of washing the lithium transition metal composite oxide with water, mixing the composite oxide with at least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate, and strontium sulfate, and heat-treating the mixture at a temperature of 150 to 280°C under vacuum conditions.

[0036] In step (1), for example, a hydroxide containing Ni, Co, and Al is obtained by a coprecipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate as raw materials. The hydroxide is calcined (oxidizing roasted) in air at 500 to 700°C for 1 to 3 hours to obtain a composite oxide containing Ni, Co, and Al. The composite oxide obtained in step (1) contains at least Ni and at least one of Al and Mn, and preferably further contains Co. The composite oxide obtained in step (1) may also contain Mo, Nb, and Si.

[0037] In step (2), the mixture of the composite oxide obtained in step (1) and the lithium compound is calcined at a temperature exceeding 700°C. The preferred range of the calcination temperature is 700 to 900°C. Calcination is preferably carried out in an oxygen stream. In step (2), an excess of the lithium compound is generally used relative to the stoichiometric ratio of the target product. Examples of the lithium compound that can be used include lithium carbonate, lithium hydroxide, lithium nitrate, and lithium sulfate. Among these, lithium carbonate and lithium hydroxide are preferred. In addition, it is preferred to crush and classify the lithium transition metal composite oxide and adjust the D50 to a predetermined range before proceeding to step (3).

[0038] In step (3), the lithium transition metal composite oxide obtained in step (2) is washed with water and subjected to solid-liquid separation to obtain a composite oxide powder having a water content of, for example, 3 to 8 mass%. At least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate, and strontium sulfate is added to the composite oxide powder and mixed. Here, these sulfate compounds may be hydrates. In addition, the amount of these sulfate compounds added is preferably 0.01 to 0.5 mol% based on the total mole number of metal elements excluding Li in the lithium transition metal composite oxide, calculated as Co, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, or Sr metal elements. At this time, tungsten oxide may be added together with the sulfate compound.

[0039] The mixed powder of the lithium transition metal composite oxide and the sulfate compound is heat-treated at a low temperature of 150 to 280°C under vacuum. The heat treatment temperature is more preferably 150 to 210°C. By heat-treating the mixed powder at a low temperature and in a vacuum state, the occurrence of cation mixing is suppressed, and a positive electrode active material in which a protective layer of an SO4-containing compound is formed on the particle surface of the lithium transition metal composite oxide is obtained. Note that, if the heat treatment in step (3) is performed in an oxygen atmosphere (air), cation mixing occurs and the initial capacity decreases.

[0040] When nickel sulfate, cobalt sulfate, and aluminum sulfate are used as the hydroxide raw materials in step (1) and titanium sulfate is added in step (3), the metal elements contained in the positive electrode active material are, for example, Li, Ni, Co, Al, and Ti. In this case, 250 mg of the positive electrode active material is added to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution, heated and dissolved at 90° C. for 2 hours, and diluted to 50 mL. The amount of S dissolved in the filtrate determined by ICP-MS is 0.002 mmol or more. A nonaqueous electrolyte secondary battery using this positive electrode active material exhibits excellent cycle characteristics.

[0041] [Negative electrode] The negative electrode 12 includes a negative electrode current collector and a negative electrode composite layer formed on at least one surface of the current collector. For the negative electrode current collector, a foil of a metal stable in the potential range of the negative electrode 12, such as copper or a copper alloy, or a film having the metal disposed on the surface layer can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably formed on both sides of the negative electrode current collector. The negative electrode 12 can be manufactured by applying a negative electrode composite slurry containing a negative electrode active material, a binder, and the like onto the negative electrode current collector, drying the coating, and then rolling the coating to form a negative electrode composite layer on both sides of the current collector.

[0042] The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions, and generally, carbon materials such as graphite are used. The graphite may be any of natural graphite such as flake graphite, lump graphite, and earthy graphite, lump artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads. In addition, metals that can be alloyed with Li such as Si and Sn, metal compounds containing Si and Sn, and lithium titanium composite oxides may be used as the negative electrode active material. Examples of compounds containing Si include SiO x Examples include Si-containing compounds represented by (0.5≦x≦1.5).

[0043] The binder contained in the negative electrode mixture layer may be a fluorine-containing resin such as PTFE or PVdF, PAN, polyimide, acrylic resin, polyolefin, or the like, as in the case of the positive electrode 11, but is preferably styrene-butadiene rubber (SBR). The negative electrode mixture layer may also contain CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, PVA, or the like. The negative electrode mixture layer contains, for example, SBR and CMC or a salt thereof.

[0044] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have a single-layer structure or a laminated structure. In addition, a highly heat-resistant resin layer such as an aramid resin, or a filler layer containing an inorganic compound filler may be provided on the surface of the separator 13.

[0045] <Example> The present disclosure will be described in further detail below with reference to examples, but the present disclosure is not limited to these examples.

[0046] <Example 1> [Preparation of positive electrode active material] The nickel-cobalt-aluminum composite hydroxide obtained by the coprecipitation method was oxidized and roasted to obtain Ni 0.85 Co 0.10 Al 0.05 A composite oxide represented by O2 was synthesized. The composite oxide was mixed with lithium hydroxide so that the molar ratio of the metal elements in the composite oxide to the Li in the lithium hydroxide was 1:1.015, and the mixture was fired at 745°C for 6 hours under an oxygen stream. The fired product was then crushed and classified to obtain a lithium transition metal composite oxide with a D50 of 12 μm. The lithium transition metal composite oxide was secondary particles formed by agglomeration of primary particles.

[0047] 1250g of lithium transition metal composite oxide was poured into 1L of water, washed with water, and separated into solid and liquid to obtain composite oxide powder with a water content of 3 to 8% by mass. The composite oxide powder was mixed with titanium sulfate, and the mixed powder was heat-treated at 180°C for 3 hours under vacuum conditions to obtain a positive electrode active material. Here, the amount of titanium sulfate added was 0.1 mol% in terms of Ti element relative to the total mole number of metal elements in the lithium transition metal composite oxide excluding Li.

[0048] The amounts of S and metal element M (Ti) eluted from the positive electrode active material were quantified by the following procedure. The measurement results are shown in Table 1 (the same applies to the following Examples and Comparative Examples). (1) 250 mg of the positive electrode active material is added to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution, and the mixture is heated and dissolved at 90° C. for 2 hours to prepare a suspension in which the active material is dispersed in the aqueous solution. (2) The suspension is filtered and diluted to 50 mL with distilled water to obtain a filtrate containing S and M. (3) Quantify S and M in the filtrate using an ICP-MS device (Hitachi High-Tech Science SPS3100).

[0049] [Evaluation of the ratio of eluted metal elements M and S] By the above-mentioned method, the partial elution amount and the total elution amount of the metal elements M and S in the obtained positive electrode active material were obtained, and the ratio ((partial elution amount / total elution amount)×100) was calculated. The measurement results are shown in Table 1 (the same applies to the following Examples and Comparative Examples).

[0050] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 100:0.75:0.6, and a positive electrode composite slurry was prepared using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. Next, the positive electrode composite slurry was applied to both sides of a positive electrode current collector made of aluminum foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to prepare a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode current collector.

[0051] [Preparation of negative electrode] The negative electrode active material is graphite and SiO x The negative electrode active material was mixed with a Si-containing compound represented by (x=1.0) in a mass ratio of 96:4. The negative electrode active material, a dispersion of styrene butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC-Na) were mixed in a solid content mass ratio of 98:1:1 to prepare a negative electrode composite slurry using water as a dispersion medium. Next, the negative electrode composite slurry was applied to both sides of a negative electrode current collector made of copper foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to prepare a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode current collector.

[0052] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 20:5:75. LiPF6 was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0053] [Battery construction] An aluminum lead was attached to the positive electrode, a nickel lead was attached to the negative electrode, and the positive and negative electrodes were spirally wound with a polyethylene separator between them to produce a wound electrode body. The electrode body was housed in a bottomed cylindrical battery case body with an outer diameter of 18.2 mm and a height of 65 mm, and the nonaqueous electrolyte was poured into it, and then the opening of the battery case body was sealed with a gasket and a sealer to produce a cylindrical nonaqueous electrolyte secondary battery.

[0054] <Comparative Example 1> A positive electrode active material and a battery were obtained in the same manner as in Example 1, except that titanium sulfate was not added in the preparation of the positive electrode active material.

[0055] [Evaluation of cycle characteristics (capacity retention rate)] Each battery of Example 1 and Comparative Example 1 was charged at 25° C. at a constant current of 0.3 It until the battery voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached the cut-off current of 70 mA. Then, the battery was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 100 times, and the ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle (capacity retention rate) was calculated. The capacity retention rate of the battery of Example 1 is shown in Table 1 as a relative value with the capacity retention rate of the battery of Comparative Example 1 taken as 100.

[0056] [Table 1]

[0057] <Example 2> In the preparation of the positive electrode active material, Ni 0.85 Co 0.05 Al 0.10 A positive electrode active material and a battery were obtained in the same manner as in Example 1, except that the composite oxide represented by O2 was used.

[0058] <Comparative Example 2> In the preparation of the positive electrode active material, Ni 0.85 Co 0.05 Al 0.10 A positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1, except that the composite oxide represented by O2 was used.

[0059] The cycle characteristics were evaluated using the batteries obtained in Example 2 and Comparative Example 2. The capacity retention rate of the battery in Example 2 is shown in Table 2 as a relative value, with the capacity retention rate of the battery in Comparative Example 2 taken as 100.

[0060] [Table 2]

[0061] <Example 3> In the preparation of the positive electrode active material, Ni 0.91 Co 0.035 Al 0.055 A positive electrode active material and a battery were obtained in the same manner as in Example 1, except that the composite oxide represented by O2 was used.

[0062] <Comparative Example 3> In the preparation of the positive electrode active material, Ni 0.91 Co 0.035 Al 0.055 A positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1, except that the composite oxide represented by O2 was used.

[0063] The cycle characteristics were evaluated using the batteries obtained in Example 3 and Comparative Example 3. The capacity retention rate of the battery of Example 3 is shown in Table 3 as a relative value assuming that the capacity retention rate of the battery of Comparative Example 3 is 100. Furthermore, the capacity retention rate under high voltage was also measured in the same manner as in the evaluation of the cycle characteristics described above, except that the voltage during charging was increased from 4.2 V to 4.3 V, and the results for Example 3 are shown as a relative value assuming that the capacity retention rate of the battery of Comparative Example 3 is 100.

[0064] [Table 3]

[0065] <Example 4> In the preparation of the positive electrode active material, Ni 0.92 Al 0.055 Mn 0.025 A positive electrode active material and a battery were obtained in the same manner as in Example 1, except that the composite oxide represented by O2 was used.

[0066] <Comparative Example 4> In the preparation of the positive electrode active material, Ni 0.92 Al 0.055 Mn 0.025A positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1, except that the composite oxide represented by O2 was used.

[0067] The cycle characteristics were evaluated using the batteries obtained in Example 4 and Comparative Example 4. The capacity retention rate of the battery in Example 4 is shown in Table 4 as a relative value, with the capacity retention rate of the battery in Comparative Example 4 taken as 100.

[0068] [Table 4]

[0069] <Comparative Example 5> In the preparation of the positive electrode active material, Ni 0.82 Co 0.15 Al 0.03 A positive electrode active material and a battery were obtained in the same manner as in Example 1, except that the composite oxide represented by O2 was used.

[0070] <Comparative Example 6> In the preparation of the positive electrode active material, Ni 0.82 Co 0.15 Al 0.03 A positive electrode active material and a battery were obtained in the same manner as in Comparative Example 1, except that the composite oxide represented by O2 was used.

[0071] The cycle characteristics were evaluated using the batteries obtained in Comparative Examples 5 and 6. The capacity retention rate of the battery in Comparative Example 5 is shown in Table 5 as a relative value, with the capacity retention rate of the battery in Comparative Example 6 taken as 100.

[0072] [Table 5]

[0073] As shown in Tables 1 to 4, the batteries of the Examples all have higher capacity retention rates after cycle testing and superior cycle characteristics compared to the corresponding batteries of the Comparative Examples. In the batteries of Comparative Examples 1 to 4, the amount of S contained in the filtrate was less than 0.002 mmol, and the ratio of the amount of elution of the metal elements M and S was less than 50%. When the amount of S contained in the filtrate is 0.002 mmol or more, and when the ratio of the amount of elution of the metal elements M and S is 50% or more, a good quality positive electrode composite layer can be formed, and the cycle characteristics of the battery are significantly improved. [Explanation of symbols]

[0074] 10 Nonaqueous electrolyte secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Battery case 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Bottom plate 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket

Claims

1. A positive electrode active material comprising a lithium transition metal composite oxide containing 85 mol % or more of Ni relative to the total number of moles of metal elements excluding Li, and at least one of Mn and Al, and containing at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr, a total amount of Mn and Al contained in the lithium transition metal composite oxide is 5 mol % or more based on the total number of moles of metal elements excluding Li contained in the lithium transition metal composite oxide; a positive electrode active material for a non-aqueous electrolyte secondary battery, the positive electrode active material being 250 mg added to 10 mL of a 17.5 mass % aqueous hydrochloric acid solution, the resulting suspension being dissolved by heating at 90° C. for 2 hours, and the resulting suspension being diluted to 50 mL; and a filtrate obtained by inductively coupled plasma mass spectrometry has a elution amount of S of 0.002 mmol or more in the filtrate.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the amount of elution of a metal element M (at least one metal element selected from Co, W, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr) contained in the filtrate is 0.0001 mmol or more.

3. 3. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 2, wherein 1 g of the positive electrode active material is added to a mixed solution of 100 mL of pure water, 1 mL of a 35 mass % aqueous hydrochloric acid solution, 0.05 mL of a 46 mass % hydrofluoric acid solution, and 0.05 mL of a 64 mass % nitric acid solution, stirred for 5 minutes, and then the mixed solution is filtered to obtain a filtrate, and a ratio ((partial elution amount / total elution amount)×100) of a partial elution amount of S and the metal element M in the filtrate determined by inductively coupled plasma mass spectrometry to a total elution amount of S and the metal element M determined in the same manner when 1 g of the positive electrode active material is completely dissolved is each 50% or more.

4. A positive electrode active material comprising a lithium transition metal complex oxide containing 80 mol % or more of Ni relative to the total moles of metal elements excluding Li, and at least one of Mn and Al, and containing at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, and Sr, a total amount of Mn and Al contained in the lithium transition metal composite oxide is 5 mol % or more based on the total number of moles of metal elements excluding Li contained in the lithium transition metal composite oxide; 250 mg of the positive electrode active material is added to 10 mL of a 17.5 mass % aqueous hydrochloric acid solution, the mixture is heated and dissolved at 90° C. for 2 hours, and the suspension is diluted to 50 mL. The filtrate obtained by inductively coupled plasma mass spectrometry has an amount of S eluted in the filtrate of 0.002 mmol or more, At least one of tungsten oxide and lithium tungstate is fixed to the particle surfaces of the lithium transition metal composite oxide.

5. 5. A non-aqueous electrolyte secondary battery comprising: a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1; a negative electrode; and a non-aqueous electrolyte.

6. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, comprising the steps of: obtaining a composite oxide by oxidatively roasting a hydroxide containing at least Ni obtained by a crystallization method; mixing the composite oxide with a lithium compound and calcining the mixed particles to obtain a lithium transition metal composite oxide; and washing the lithium transition metal composite oxide with water, mixing the composite oxide with at least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate, and strontium sulfate, and heat-treating the mixture at a temperature of 150 to 280° C. under vacuum conditions.

Citation Information

Patent Citations

  • Positive electrode activator for lithium secondary battery, positive electrode of lithium secondary battery using the same, and lithium secondary battery

    JP2004288501A

  • Lithium-ion secondary battery

    JP2006351379A

  • Method of manufacturing positive electrode active material, and positive electrode active material

    JP2010040383A

  • Lithium metal composite oxide powder with suppressed gas generation

    WO2018172272A1